Evaluation of Solvent-Free Microwave Extraction Conditions on Essential Oils from Allium cepa Through Chemometric Analysis - Ikram, Rabia; Low, Kah Hin; Hashim, Najihah Mohd; Ahmad, Waqas; Nasharuddin, Muhammad Nazil Afiq (Bentham Science Publishers, 2018)
Background: The feasibility of applying methods or the extraction of Allium cepa essential oils using solvent-free microwave extraction (SFME) has been compared to hydro-distillation (HD) process. Parameters of extraction were investigated using a rational design of experiment screening. Objective: To screen the important factors that may influence the quantity and/or quality of the extracts derived from Allium cepa Method: A no. of 13 experiments were performed based on the screening process. The key parameters, such as power (350/500 W), size of the sample (chopped/sliced), quantity (500/1000 g), time of extraction (25/50 min.) and water ratio (20/50 mL) were selected based on the limitation of the instrument. The essential oils derived from Allium cepa were characterized by GC-MS analysis. Results: The commonly collected constituents via SFME and HD are 3,4-Dimethylthiophene, Disul-fide, methyl propyl, Dithiolane, 2,4-Dimethyl-5,6-dithia-2,7-nonadienal, 4,6-Diethyl-1,2,3,5-tetrathiolane, 5,7-Diethyl-1,2,3,4,6-pentathiepane (sulfur-containing compounds) and Methoxyacetic acid, cyclopentyl ester, 2-Propenoic acid, 2-methyl-, octyl ester (fatty acid esters). Conclusion: A pragmatic relationship between the variations of extraction parameters has been studied. Results suggested and verified that among the factors, Power and time of extraction influence the process of extraction significantly.